2022
DOI: 10.3390/pathogens11101122
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Telemedicine in the Diagnosis of Erythema Migrans during the COVID Pandemic: A Comparison with In-Person Diagnosis in the Pre-COVID Era

Abstract: Background: Erythema migrans (EM) is the hallmark manifestation of the Lyme borreliosis (LB), and therefore its presence and recognition are sufficient to make a diagnosis and to start proper antibiotic treatment to attempt to eradicate the infection. Methods: In this study we compared the clinical data of 439 patients who presented an EM either according to the diagnostic modality through physical assessment or through telemedicine. Conclusions: Our data clearly show that telemedicine for EM diagnosis is usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…Our studies confirm that children have a distinct clinical presentation from adults. This is also a consequence of the different location of the tick bite in children, which as reported also by other authors is often on the head (54,55). We also observed that there is a gender effect on clinical presentation, with females presenting more often with EM or ACA than males, while males present more often with neurological signs or arthritis than females.…”
Section: Discussionsupporting
confidence: 80%
“…Our studies confirm that children have a distinct clinical presentation from adults. This is also a consequence of the different location of the tick bite in children, which as reported also by other authors is often on the head (54,55). We also observed that there is a gender effect on clinical presentation, with females presenting more often with EM or ACA than males, while males present more often with neurological signs or arthritis than females.…”
Section: Discussionsupporting
confidence: 80%
“…However, EM is not systematically detected and only non-characteristic symptoms linked to stages 2 and 3 (Lyme neuroborreliosis, carditis, or arthritis) can be expressed [ 1 , 22 ]. It is important to emphasize that the risk of the appearance of other symptoms from LB (especially neurologic and articular manifestations) is significantly reduced after the recognition of EM and the rapid initiation of antibiotic treatment [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence is increasing in different Western European countries together with a geographical expansion of the disease into previously non-endemic areas (Beltrame et al, 2021). Although we are not describing the incidence of the disease, cases increased in the observation period with a maximum of observations in 2020, possibly due to the COVID pandemic and the use of telemedicine in diagnosing EM (Trevisan et al, 2022). In Italy, during the pandemic, patients could not reach hospitals for dermatological evaluation, and after a telephone interview with the doctors, they sent their pictures of the lesions by e-mail or showed them on a video call.…”
Section: Discussionmentioning
confidence: 86%
“…Patients' data were gathered from 01/01/2010 to 30/08/2022 in the participating centers in Friuli-Venezia Giulia, Liguria, Lombardy, Emilia-Romagna, and Campania, as shown in Figure 1. During the COVID pandemic, telemedicine has also been used (Trevisan et al, 2022) for diagnosis, especially for EM lesions. In each center, the following diagnostic criteria were applied for LB diagnosis:…”
Section: Methodsmentioning
confidence: 99%